0.6(2x+7)-4.3x=5.1

Simple and best practice solution for 0.6(2x+7)-4.3x=5.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6(2x+7)-4.3x=5.1 equation:


Simplifying
0.6(2x + 7) + -4.3x = 5.1

Reorder the terms:
0.6(7 + 2x) + -4.3x = 5.1
(7 * 0.6 + 2x * 0.6) + -4.3x = 5.1
(4.2 + 1.2x) + -4.3x = 5.1

Combine like terms: 1.2x + -4.3x = -3.1x
4.2 + -3.1x = 5.1

Solving
4.2 + -3.1x = 5.1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4.2' to each side of the equation.
4.2 + -4.2 + -3.1x = 5.1 + -4.2

Combine like terms: 4.2 + -4.2 = 0.0
0.0 + -3.1x = 5.1 + -4.2
-3.1x = 5.1 + -4.2

Combine like terms: 5.1 + -4.2 = 0.9
-3.1x = 0.9

Divide each side by '-3.1'.
x = -0.2903225806

Simplifying
x = -0.2903225806

See similar equations:

| 2(3)-15= | | -71+8x-27-2x= | | -71+8x+5x+48= | | 11c+47+21m+88(x)=19b | | 0.5x-8.3/2.2=5.5 | | -46+2x-71+8x= | | 0.50+7=15x+6 | | 7p+28q-70=0 | | -25+6x-46+2x= | | -z^2-4z+7=0 | | -46+2x+5x+48= | | 0.45t^2-2t+1=0 | | 5(x-3)+7=3x+2(-3+x) | | -s+6+3s=8s | | -20+z=4 | | 7b=11+95+41 | | -32-6x+8x-14= | | 1.126=2x+3 | | 2p+1=3p+7 | | -14x-39+5x+48= | | f(x)=3x^2+7x+1 | | -8y+7-5y=-18 | | 8x-14+5x+48= | | k^2+12k-14=0 | | -1/9n=17 | | 3(2+x)=4-(x+2) | | 7x+27=4x+12 | | -28=4h-3h | | X+(-7y)+(-4x)+8y= | | -20=4(8z-2) | | 2x+6y-8+19x=0 | | (2x-7)2=81 |

Equations solver categories